Hepatoprotective and anti-inflammatory cytokines in alcoholic liver disease - Gao, Bin (Journal of gastroenterology and hepatology, 2012)
The activation of innate immunity by various factors (e.g. lipopolysaccharide and complements) plays an important role in initiating and promoting alcoholic liver injury via the stimulation of Kupffer cells to induce oxidative stress and to produce pro‐inflammatory cytokines (e.g. tumor necrosis factor [TNF]‐α) that cause hepatocellular damage. Accumulating evidence suggests that the activation of innate immunity also stimulates Kupffer cells to produce the hepatoprotective cytokine interleukin‐6 (IL‐6) and the anti‐inflammatory cytokine IL‐10 during alcoholic liver injury. IL‐6 protects against alcoholic liver injury via the activation of signal transducer and activator of transcription 3 (STAT3) and the subsequent induction of a variety of hepatoprotective genes in hepatocytes. IL‐10 inhibits alcoholic liver inflammation via the activation of STAT3 in Kupffer cells/macrophages and the subsequent inhibition of liver inflammation. Recent studies have suggested that IL‐10 may play a dual role in controlling ethanol‐induced steatosis and liver injury via the inhibition of the pro‐inflammatory cytokine TNF‐α, thereby ameliorating alcoholic liver injury, or via the inhibition of the hepatoprotective cytokine IL‐6, thereby potentiating alcoholic liver injury. IL‐22 is another important hepatoprotective cytokine that protects against acute and chronic alcoholic liver injury by binding to a receptor complex composed of IL‐10R2 and IL‐22R chains on the surfaces of hepatocytes. Finally, IL‐22 treatment is a potential therapeutic option for treating severe forms of alcoholic liver disease because of its antioxidant, antiapoptotic, antisteatotic, proliferative, and antimicrobial effects, as well as the potential added benefit of few side effects.